2020
DOI: 10.1108/pr-08-2019-0456
|View full text |Cite
|
Sign up to set email alerts
|

The role of the human dimension in organizational agility: an empirical study in intensive care units

Abstract: PurposeThe purpose of this paper is to analyse the role of hospital leaders and high-performance work practices (HPWPs) in intensive care units (ICUs) in organizational agility and its impact on healthcare personnel satisfaction.Design/methodology/approachThis study was carried out in three ICUs of an important Spanish public hospital, one for adults, one paediatric and one neonatal. The unit of analysis was ICUs personnel (324 individuals: 14.5%, 48.8% and 36.7% from the categories of doctors, nurses and nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…From a human resource perspective, managers can use flexible leadership styles to foster employees' creativity and to reach organizational agility (Singh et al, 2013). Furthermore, Melián-Alzola et al (2020) found that organizational agility would be achieved through the job satisfaction of essential workers.…”
Section: Organizational Agilitymentioning
confidence: 99%
See 3 more Smart Citations
“…From a human resource perspective, managers can use flexible leadership styles to foster employees' creativity and to reach organizational agility (Singh et al, 2013). Furthermore, Melián-Alzola et al (2020) found that organizational agility would be achieved through the job satisfaction of essential workers.…”
Section: Organizational Agilitymentioning
confidence: 99%
“…Organizational agility generally refers to an, "organization's ability to effect on market changes and take timely actions and offer new solutions so as to cope with a dynamic and complex environment" (Overby et al, 2006, p. 131). Although the existence of agility has been demonstrated in previous studies (Cegarra-Navarro & Martelo-Landroguez, 2020), particularly regarding information technology management (Melián-Alzola et al, 2020), Di Minin et al (2014) stated that agility is a strategic tool for managing organizations as it refers to an organizations' quick and rightful response to the external environments. In this field, Darvishmotevali and colleagues (2020) argued that in highly dynamic and complex environments, organizations must reduce the bureaucracy to manage the challenges of uncertainty.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…We base our discussion and conclusions on a meta-analysis of the Web of Science’s Collection in the period 1997–2021 to develop research propositions and outline some organizational changes and analytical tools to pilot transitions to agile. The focus, first, on HR flexibility is because employee matters are one of the main pillars of agile innovation and a driver of organizational changes (Krstić et al , 2018; Walter, 2021; Melián-Alzola et al , 2020). The way to manage HR flexibility is a key element of innovation processes as the tacit knowledge that resides in multi-skilled employees and external research and development (R&D) experts is required to accelerate sprints (iterations in agile innovation).…”
Section: Introductionmentioning
confidence: 99%